Chemically modified Sb2O3, a new member of high solar-reflective material family, incorporating with ASA (acrylonitrile-styrene-acrylate copolymer) for fabrication of cooling composite with lower wetting behavior. (1st April 2019) - Qi, Yanli; Zhang, Jun
Abstract: In this study, it is observed that antimony trioxide (Sb2 O3 ) performs great potential as new solar-reflective additive to cool materials with higher security for its synergistic flame-retarding application. The optimal content of Sb2 O3 into poly (acrylonitrile-styrene-butyl acrylate) (ASA) resin has been investigated, accompanied with the investigation of the effect of hydrophobic modification on Sb2 O3 on the composite surface wettability. The cooling effect of the composite incorporated with the addition of 10 wt% modified Sb2 O3, which has a solar reflectance of 68.4%, is estimated to be 13 °C higher than uncovered device on a summer sunny day. Simultaneously, the water contact angle of the abovementioned sample increases to 97°, which is 19° higher than that of the sample introduced with 10 wt% unmodified Sb2 O3 . It is envisioned that widely applicable composited cool materials can be achieved with the assistance of modified Sb2 O3 particles. Highlights: The cool material performs high NIR and solar reflectance. The cool material performs high cooling efficiency. A lower wetting behavior is achieved by adding chemically modified Sb2 O3 . The ASA/Sb2 O3 composite exhibits excellent weather resistance. Improved mechanical properties are achieved for enhanced interface adhension.